School Climate, Teacher Characteristics, and School Discipline: Evidence From New York City - Luis A. Rodriguez; Richard O. Welsh; Chelsea Daniels (SAGE Publishing, 2024)
School discipline is a salient problem of educational policy and practice. Teachers play an important role in the production and disruption of racial inequities in school discipline, yet there remains a need to disentangle the relationship between teacher characteristics, their perceptions of school climate, and school discipline patterns. This study uses longitudinal data representing over one thousand public middle and high schools in New York City and linear regression methods to examine the relationship between teachers' perceptions of school climate, teacher characteristics, and the rates of and disparities in suspensions. Overall, results indicate more positive teacher perceptions of school climate, higher years of teaching experience, and a greater share of Black teachers are independently associated with lower rates of office referrals and suspensions, overall and especially for Black and Latinx students. The study concludes by discussing implications for teacher education and on-the-job support as well as school leadership.